Language and nationality social inferences, cultural differences and linguistic misconceptions - Bortone, Pietro (Bloomsbury Academic, 2023)
"Language both reflects and reproduces social inclusions and exclusions; the language a person speaks, and the way that they speak it, signals membership of social groupings. But what role does language play in the formation and perpetuation of our ideas about ethnicity and nationality? Language and Nationality investigates this question and the pernicious consequences of the notion that ethnicity, nationality and language are naturally and exclusively connected. Beginning with an examination of how language helps to shape and influence a person's sense of individual and collective identity, Pietro Bortone discusses the role that language has, or is believed to have, in the formation of ethnic and national communities. Showing how language, as both a channel for a national(ist) outlook and a national(ist) symbol in itself, came to be seen as the key indicator of both ethnicity and nationality, this book uncovers the far-reaching consequences the mistaken belief that a nation has a single, intrinsic language has had, and how the politicization of language can unite, but also dramatically divide, communities. Whilst language plays, and has always played, a major role in expressing and defining people's identities, this book demonstrates that the idea that language, ethnicity and nationality are intrinsically linked is a misleading result of our intellectual history, and one which has had a significant cost"--$cProvided by publisher.